2005
DOI: 10.1093/ps/84.2.194
|View full text |Cite
|
Sign up to set email alerts
|

Do low-density diets improve broiler breeder welfare during rearing and laying?

Abstract: Low-density diets may improve welfare of restricted fed broiler breeders by increasing feed intake time with less frustration of feed intake behavior as a result. Moreover, low-density diets may promote satiety through a more filled gastrointestinal tract, and thus feelings of hunger may be reduced. Broiler breeders were fed 4 different diets during the rearing and laying periods. Behavioral and physiological parameters were measured at different ages as indicators of hunger and frustration of the feeding moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 26 publications
3
35
0
5
Order By: Relevance
“…D 'Eath et al (2009) emphasised that comparisons of feeding schedules resulting in differences in live weight do not compare like with like. De Jong et al (2005b) found some welfare improvements in terms of reduced hunger and frustration when energy content of the diet was lowered by 23%, but they conclude that more extreme diet modifications are required to improve substantially the welfare of growing broiler breeders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…D 'Eath et al (2009) emphasised that comparisons of feeding schedules resulting in differences in live weight do not compare like with like. De Jong et al (2005b) found some welfare improvements in terms of reduced hunger and frustration when energy content of the diet was lowered by 23%, but they conclude that more extreme diet modifications are required to improve substantially the welfare of growing broiler breeders.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to feed broiler breeders with highfibre diets in order to increase satiety and improve welfare have been studied using different kinds of fibre sources (Zuidhof et al, 1995;De Jong et al, 2005b;Sandilands et al, 2006). However, previous attempts to feed high-fibre diets to growing broiler breeders have often concentrated on one fibre source at a time (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The values in this experiment are comparable to this value. Heterophil to lymphocyte ratios have been shown to assess levels of stress (Gross and Siegel 1983;de Jong et al 2005). Previous research suggests that providing high levels of dietary fibre leads to improvement of the welfare of broiler breeders as indicated by H:L ratios (Zuidhof et al 1995;Hocking et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This may compromise animal welfare, and cause abnormal behaviour, such as spending more time resting than slower growing genotypes (Nielsen et al, 2003). Some studies discuss the strategy of providing growing female broiler breeders with low density diets as an alternative to feed restriction (De Jong et al, 2005), and reported reduced hunger and frustration, observed as reduced stereotypic and tail pecking and increased dust bathing and other comfort behaviours compared with those fed standard restriction diets (Nielsen et al, 2011). Further research is needed, however, to study if high fibre diets can increase Sustainable poultry production development: M. Vaarst et al…”
Section: Animal Welfarementioning
confidence: 99%